Prevalence of subacromial-subdeltoid bursitis in shoulder pain: an ultrasonographic study - Draghi, Ferdinando (J Ultrasound, 2015)
PURPOSE: The presence of the subacromial-subdeltoid (SASD) bursa inflammation has recently been proposed as a primary radiologic factor predicting persistent limitation and pain in operated patients. The aim of the study was to verify the hypothesis that pain, or increased shoulder pain, could be associated with SASD bursitis not only in operated patients but also in general population. METHODS: A consecutive series of 1940 shoulder ultrasound examinations were performed by our Department over a 5-year period using linear multi-frequency probes. All reports of examination executed for shoulder pain were reviewed. The video clips were independently reviewed by two radiologists: effusion in the SASD bursa and the presence of other pathological conditions were evaluated and confirmed. RESULTS: A total of 1147 shoulder video clips were re-evaluated, and 1587 pathologies were detected; 65.5 % of patients had only one pathology, 30.4 % had two and 4.1 % presented three pathologies. The difference between the group with and without effusion is statistically significant for acromioclavicular joint arthritis, supraspinatus tendon calcific tendinopathy, full-thickness and superficial tear of the supraspinatus, traumas and rheumatoid arthritis with a p value <0.01. CONCLUSIONS: Our study shows that the effusion in the SASD bursa is frequently associated with shoulder pain often independently from the underlying pathology; further studies are needed to confirm the statistical significance of this relationship by clarifying possible confounding factors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40477-015-0167-0) contains supplementary material, which is available to authorized users.